Model Pengembangan Kurikulum Adaptif Pada Madrasah Ibtidaiyah Inklusif - Nur Jannah; Syarifatul Marwiyah (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2020)
The existence of an Extraordinary School as one of the educational institutions that is specifically intended to educate children with special needs in reality is still not able to fully accommodate the education of children with special needs. The increasing number of children with special needs while the existence of Extraordinary Schools is limited in each district in Indonesia has caused many parents to send their children with special needs to formal education institutions, one of them in Madrasahs. This phenomenon requires Madrasas to adjust to their presence by becoming an institution that is friendly and inclusive of students whatever the conditions. One such effort is to develop an inclusive Madrasah curriculum that is a curriculum that suits the needs of children with special needs. The following article discusses the Adaptive Curriculum Development Model with a focus on discussion on Inclusive Madrasah Ibtidaiyah with the aim of developing an adaptive curriculum in which there are models of duplication, modification, substance and omission. All models of curriculum development can be an option to be implemented in an inclusive Ibtidaiyah Madrasah, depending on which model is considered the most appropriate for the conditions of students in Madrasas and which is possible to apply, this is because each Madrasah has different conditions between one and the other so they can implement a curriculum model that suits their students' needs.